Produktivitas Pekerja Konstruksi ditinjau dari Supervisi, Beban Kerja, dan Burnout - Cilda Thesisa Ilmawan Dzinnur; Arif Rachman Putra (Journal of Trends Economics and Accounting Research, 2022)
Productivity is important to achieve construction project performance through productive workers who must be maintained without neglecting and compromising the health and safety of workers. This is because there are many productivity issues that are not achieved due to poor human resource management practices in the industry. For this reason, through this study, work productivity will be identified based on supervision, workload and burnout. Observations were made at a construction company from Surabaya. There are 258 target respondents who come from construction workers in the working area of West Surabaya. The sampling technique is accidental sampling. A total of 210 valid questionnaires were finally obtained so as to meet the required number of samples. The findings from this study are that supervision plays an effective role in shaping work productivity. Workload has a real and negative effect on work productivity. This is also the same as burnout results which significantly negatively affect work productivity.